Security in the Indo-Pacific: The Asianisation of the regional security architecture - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2022)
Since the Korean War of 1950-53, the security architecture of the region previously referred to as the 'Asia-Pacific' has been based on a US-led system of bilateral alliances known as the 'hub-and-spokes' system. A multilateral system of collective defence, similar to NATO in Europe, has not existed in the region. In 2014, the People's Republic of China under Xi Jinping began to develop its own ideas for reshaping the regional security system. Xi called the hub-and-spokes system a relic of the Cold War and called for a regional security architecture 'by Asians for Asians'. The 'Indo-Pacific' is widely regarded as a strategy to counter a Sinocentric restructuring of the region. The majority of actors involved conceives its security architecture as an antagonistic order in which security is established against, and not with, China. This architecture is more 'Asianised' than before. The region's US allies are gaining significance in relation to Washington. What's more, bilateral and minilateral partnerships outside the hub-and-spokes system are becoming increasingly important, for example those involving states such as India or Indonesia. Structurally, bilateral alliances and partnerships dominate. They are increasingly supplemented by minilateral formats such as AUKUS or the Quad. For the EU and its member states, all this means that realising the idea of an inclusive Indo-Pacific has become a distant prospect. The effective multilateralism propagated by the EU is also gradually falling behind as the regional security architecture is increasingly being transformed into a web of bilateral and minilateral cooperation formats.
Keywords: 320; Australia; India; Indonesia; USA; China; hub and spoke; ASEAN; Indo-Pacific; AUKUS; Quad; minilateral formats; security architecture